Stress Management Among Nurses In Dealing With Job Stress In The Intensive Care Unit (Icu) At RSUD Tgk Chik Ditiro Sigli - Jauhariyadi Jauhariyadi; Fauziah Fauziah; Syamsul Bahri; Fitriani Fitriani; Anwar Anwar (International Journal of Health Engineering and Technology, 2026)
Work stress among nurses is a significant issue, particularly in high-intensity units such as the Intensive Care Unit (ICU), where job demands are complex and emotionally challenging. Nurses in the ICU are required to provide continuous monitoring, respond quickly to critical patient conditions, and operate advanced medical equipment, all of which may contribute to increased stress levels. This study aimed to describe stress management strategies used by nurses in dealing with work-related stress in the ICU at RSUD Tgk Chik Ditiro Sigli. A quantitative descriptive design was employed involving 30 nurses working in the ICU. The findings showed that the majority of nurses applied good physical stress management strategies (83.3%), good cognitive strategies (66.7%), and good social strategies (90.0%). However, emotional strategies were mostly categorized as moderate (66.7%). These results indicate that ICU nurses predominantly utilize effective stress management approaches, particularly social and physical strategies, in coping with job stress. Strengthening emotional coping skills through training and organizational support is recommended to further enhance nurses’ psychological well-being and maintain the quality of patient care.